Experimental study of jacket height and reinforcement effects on seismic retrofitting of concrete columns. (June 2021) - Zaiter, Ali; Lau, Tze Liang
Abstract: This study evaluates the jacket height and reinforcement effects on reinforced concrete (RC) square columns retrofitted with normal concrete. Five one-third scale columns with non-ductile reinforcement were tested. Four columns were retrofitted with RC jackets with quarter height (h/4) and half height (h/2) where h is the column height. Subjected to cyclic loading, the failure pattern, lateral load capacity, stiffness, ductility, and energy dissipation of the column were investigated. Results show that increasing the jacket height significantly affected the failure pattern and lateral load capacity. Increasing the jacket height from h/4 to h/2 showed a pronounced shear failure and steeper diagonal cracks. Columns jacketed with h/2 jacket almost doubled the original lateral load capacity. The difference in the lateral load capacity of columns with h/2 jackets and h/4 jackets was above 23%. The jacket reinforcement confinement reduced the level of jacket damage and increased the damage and concrete crush in the column above the jacket. However, the unreinforced jacket increased the jacket damage and reduced the damage above the jacket. The jacket reinforcement increased the lateral load capacity by the shear transfer mechanism while the jacket height enhanced the energy dissipation of the jacketed columns by arch (strut) action. In addition, the jacket height and reinforcement increased the column's stiffness and consequently, the stiffness irregularity produced short column shear failure above the jacket. From the results, a simplified analytical model was developed to predict the structural capacities of the jacketed column.